Validity of maternal self-reported antibiotic consumption in children: A population-based study - Javad Nazari; Nahid Chezani-Sharahi; Yeganeh Karimi; Mobin Naghshbandi; Rahmatollah Moradzadeh (International Journal of Africa Nursing Sciences)
Background: Validity of the self-reported data is very important. The primary objective of this study is to evaluate the accuracy of maternal self-reported antibiotic use in children aged 0–6 years in Iran by comparing it with prescription data from insurance records. Methods: A total of 1483 children aged between 0 and 6 years were recruited in this study. We used stratified random sampling to determine recruitment criteria. Self-reported data of consumption of antibiotics was collected by interviewing with mothers. The prescribing data gathered through using the information registered in the insurance records as gold standard. Statistical parameters which were calculated included Sensitivity, Specificity, PPV and NPV. The confidence interval of 95 % was computed for these indices. Results: Mean age of the children was 2.1 ± 1.5 years, and 52 % were girls. Maternal self-reported consumption of antibiotic among children estimated 62 %. Consumption of antibiotic based on the insurance records was seen in 3 % of the participants. The Sensitivity of maternal self-reported consumption of antibiotic among children was 72 % (95 % CI 57.5–83.8) and the PPV was 3.89 % (95 % CI 2.74–5.34). Specificity and NPV were calculated to be 37.9 % (95 % CI 35.4–40.5) and 97.5 % (95 % CI 95.8–98.6) in total population. In the parameters including suffering from chronic diseases, Self-reported awareness of antibiotic resistance, Mother as housekeeper, Specificity and NPV varied between 18.7 % and 97.5 % and the Sensitivity and PPV of were obtained between 2.86 % and 81.3 %. Conclusion: The validity of self-reported antibiotic consumption in this population was low. Thence, self-reported antibiotic consumption should be given with discretion.